2016
DOI: 10.4322/rca.2353
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and initial growth of Hancornia speciosa (Gomes) seedlings with different substrates and water availability

Abstract: Hancornia speciosa is a promising fruit species due to the high protein content of its fruit. However, there is little information about its production, with a lack of information concerning the germination of its seeds and initial seedling growth. The aim of this study was to evaluate water availability and suitable substrates for its seedling emergence and production. The seeds were deposited in tubes, containing the following substrates: Distroferric Red Latosol (L); Latosol+Sand (L+A); Latosol+Bioplant  (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 16 publications
3
18
0
1
Order By: Relevance
“…This result has been reported in the literature for other species, as this mixture presents materials that enable good porosity and drainage in their composition, which allow the movement of water and air in the substrate and favor the germination and emergence (FORNASIERI FILHO, 1992;SILVA et al, 2009;JEROMINE, 2013;GORDIN et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…This result has been reported in the literature for other species, as this mixture presents materials that enable good porosity and drainage in their composition, which allow the movement of water and air in the substrate and favor the germination and emergence (FORNASIERI FILHO, 1992;SILVA et al, 2009;JEROMINE, 2013;GORDIN et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Gordin et al (2016) observed in their review that, as the leaf expansion is a process 520 FLORESTA, Curitiba, PR, v. 47, n. 4, p. 513 -522, out/dez. 2017.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations